Pemenuhan Jaminan Perlindungan Pesepeda di Kota Sepeda - Diena Kurniasih (LPPM Universitas Sains dan Teknologi Komputer, 2023)
At this time the number of bicycle users in the city of Yogyakarta is still quite a lot. People in the city of Yogyakarta use bicycles for various activities. At present the majority of bicycles are used as entertainment or sports. However, it is not uncommon to find people still using their bicycles to work, go to school, and as the main means of transportation to where they want to go. People using bicycles in the city of Yogyakarta can be divided into two, namely for those who use bicycles as their main transportation such as going to school or work or daily activities that are quite close such as shopping to the market. Others are for those who use bicycles as entertainment and sports. The number of cyclists who use their bicycles as the main means of transportation is currently starting to switch to motorized vehicles to go where they want